2005
DOI: 10.1038/sj.gene.6364211
|View full text |Cite
|
Sign up to set email alerts
|

Allelic effects on gene regulation at the autoimmunity-predisposing CTLA4 locus: a re-evaluation of the 3′ +6230G>A polymorphism

Abstract: Genetic variation at a linkage disequilibrium block encompassing the cytotoxic T-lymphocyte antigen-4 (CTLA4) gene influences susceptibility to autoimmunity, but identifying the polymorphism(s) responsible for this effect has been challenging. Recently, a single-nucleotide polymorphism (SNP) located 3 0 to the known polyadenylation site of CTLA4 ( þ 6230G4A) and strongly associated with autoimmune disease was reported to regulate levels of soluble CTLA4 isoform (sCTLA4) but not the full-length isoform. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 22 publications
2
24
1
1
Order By: Relevance
“…Atabani and colleagues (6) confirmed this observation in their study of CTLA4 isoforms in purified T cells and demonstrated an association of CT60 and sCTLA4 mRNA levels with the frequency of CD4 ϩ CD25 ϩ regulatory T cells in healthy human volunteers. Importantly, the genotype-dependent difference in the expression of soluble CTLA4 transcripts may be T cell-specific because it is not observed when steady-state CTLA4 mRNA from peripheral blood mononuclear cells, rather than purified T cells, are studied (23). The orthologous CTLA4 region in the mouse also is associated with autoimmune diabetes in the NOD mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Atabani and colleagues (6) confirmed this observation in their study of CTLA4 isoforms in purified T cells and demonstrated an association of CT60 and sCTLA4 mRNA levels with the frequency of CD4 ϩ CD25 ϩ regulatory T cells in healthy human volunteers. Importantly, the genotype-dependent difference in the expression of soluble CTLA4 transcripts may be T cell-specific because it is not observed when steady-state CTLA4 mRNA from peripheral blood mononuclear cells, rather than purified T cells, are studied (23). The orthologous CTLA4 region in the mouse also is associated with autoimmune diabetes in the NOD mouse.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of sCTLA4 to flCTLA4 mRNA splice forms in unstimulated CD4 T cells was 50% lower in +6230G/G positive disease-susceptible individuals compared with A/A protected individuals, suggesting that this 6.1kb region determines splicing efficiency and production of sCTLA4, with the +6230G disease-susceptibility haplotype producing less sCTLA4 transcripts than the +6230A haplotype. However, Anjos et al (33) reported no observable effect of the +6230 SNP on the expression of either sCTLA4 or flCTLA4 using allele-specific single-nucleotide primer extensions. We also failed to find a correlation between +6230 alleles and serum sCTLA4 levels, regardless of susceptibility to AIP in +6230G/G.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, reports on the association of CTLA-4 with MS have been inconsistent. [32][33][34][35][36][37][38][39][40][41] However confusing the association of CTLA-4 with MS, it is worth considering this gene as a potential contributor to the disease.…”
Section: Ctla-4: a General Marker Of Autoimmunity?mentioning
confidence: 99%